Phytosynthesis of Titanium Dioxide Nanoparticles Using King of Bitter Andrographis paniculata and Its Embryonic Toxicology Evaluation and Biomedical Potential - S. Rajeshkumar; J. Santhoshkumar; Leta Tesfaye Jule; Krishnaraj Ramaswamy (Bioinorganic Chemistry and Applications)
Phytosynthesis particles are the efficient activity of biomedical and environmental. In this present study, the green synthesis of titanium dioxide (TiO2) nanoparticles using the king of bitter herbal plant Andrographis paniculata was synthesized and characterized using XRD, SEM, HRTEM, AFM, and antimicrobial, antioxidant, and antidiabetic activities. The size of the particles HRTEM shows 50 nm, and SEM shows the spherical shape, which reveals the synthesis of TiO2 nanoparticles. XRD spectrum shows crystallinity of nanoparticles, and an average size is calculated about 22.97 nm. The phytosynthesis TiO2 shows the antioxidant and antidiabetic activities. Similarly, toxicity studies have demonstrated the hatching and viability LD 50 value of TiO2 250 μg/L. The current study’s findings suggested that phytosynthesis TiO2 using extract of Andrographis paniculata exposure to potential hazard factors to biomedical and environmental uses.